1967
DOI: 10.1085/jgp.50.5.1125
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Force-Velocity Relation for Muscle Contraction in the Length Region, ll0

Abstract: Considerable attention has been directed to the characteristic force-velocity relation discovered by A. V. Hill in the study of muscle kinematics. Models of contractile process were tested on the basis of their compatibility with the Hill equation. However, almost all the isotonic data have been restricted to one length, 10, the maximum lengthwith almost no resting tension; the velocities measured are those initial values when the load begins to move. The force-velocity curve extrapolates to zero velocity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…These values of about 1.8 kg/cm 2 are within the lower range of P o values generally obtained in mammalian skeletal muscle (11)(12)(13)(14)(15). Using the highest mean value for the P' o (1.08 kg/cm 2 ) as experimentally obtained in the heart muscle at the optimal length of the length-tension relation (15) and correcting this value for the SE extension by the factor 0.6 derived from the present study, a maximal isometric tension of 1.80 kg/cm 2 would be obtained in heart muscle.…”
Section: Discussionsupporting
confidence: 85%
“…These values of about 1.8 kg/cm 2 are within the lower range of P o values generally obtained in mammalian skeletal muscle (11)(12)(13)(14)(15). Using the highest mean value for the P' o (1.08 kg/cm 2 ) as experimentally obtained in the heart muscle at the optimal length of the length-tension relation (15) and correcting this value for the SE extension by the factor 0.6 derived from the present study, a maximal isometric tension of 1.80 kg/cm 2 would be obtained in heart muscle.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, it provides new interpretations of some experiments reported in the literature. Buchthal (1942), Mar~chal (1955), Del~ze (1961), and Matsumoto (1967) have shown that the 'isotonic' length-tension diagram is not the same as the 'isometric' length-tension diagram. The latter is obtained by tetanizing the muscle isometrically at various lengths, the former by recording the active shortening of muscles pulling a free-hanging load.…”
Section: Discussionmentioning
confidence: 99%
“…The tension-length diagram obtained" by tetanizing the muscle isometrically at various lengths is not the same as that obtained by recording the active shortening of muscles which pull a free-hanging load (Buchthal, 1942;Mar6chal, 1955;Delbze, 1961;Matsumoto, 1967). The velocity of isotonic shortening measured at some given length depends on the starting length (Carlson, 1957;Bahler et al, 1968).…”
Section: Introductionmentioning
confidence: 91%
“…~la.6" F o r isometric tension developed at l e n g t h , / 0 , a n d isotonic contraction after- (Matsumoto, 1967), and T = 0.109 sec when l/lo = 1.0. Substituting these values in the above equation, l0 dP 30.6 P F-~o dl----~ = ~ + 7.65 (see Fig.…”
Section: If the Exponential Tension-time Course Is Approximately Corrmentioning
confidence: 99%
“…Isotonic contractions were studied with a series of afterloads and the shortenings were imposed at intervals no shorter than 10 rain. For each muscle, a whole family of shortening vs. time curves was obtained, each curve within the series differing from the others in the amount of afterload (Matsumoto, 1965(Matsumoto, , 1967.…”
Section: E X P E R I M E N T a Lmentioning
confidence: 99%